Workshop Pengelolaan Referensi Ilmiah Dengan Mendeley Untuk Penyelesaian Skripsi Mahasiswa Pendidikan Ekonomi - Putri, Windy Utami; Alexandro, Rinto; Oktaria, Merisa; Hariatama H, Fendy; Putra, Kharisma Nugraha (LPPM Universitas Palangka Raya, 2023)
Scientific work is one of the important elements for higher education in maintaining its reputation and increasing the achievements. It is very important to produce good and quality scientific work. One of the indicators is freedom from plagiarism. This can be achieved by providing knowledge to students in quoting and managing student scientific references. One application to facilitate the management of scientific references is Mendeley. The purpose of holding community service is to increase student digital literacy regarding reference management and to help them implement it in making their student theses, which they will need to complete their final assignments. The training was held at the Merah Putih Building, University of Palangka Raya, with the target participants being undergraduate students of the Economics Education Study Program, Faculty of Teaching and Education, University of Palangka Raya. The results of the participants' activities were full of enthusiasm and high motivation to take part in scientific reference management workshops with Mendeley for the completion of their college assignments and theses.